Nilai-Nilai Islami Dalam Komunikasi Organisasi - Moh. Fawaid; Ali Wahdi; Ainul Yaqin (Al-Abshar: Journal of Islamic Education Management, 2025)
Organizational communication is a fundamental element in ensuring coordination, efficiency, and sustainable institutional performance. However, contemporary organizational communication models often emphasize technical effectiveness while giving limited attention to ethical and spiritual dimensions. This study aims to examine the integration of Islamic values into organizational communication and to analyze their contribution to the development of an ethical, transparent, and value-based communication model. The research employs a qualitative approach using a comprehensive literature review of classical Islamic sources, the Qur'an, Hadith, and contemporary scholarly publications on organizational communication and Islamic management. Data were collected through document analysis and analyzed using thematic content analysis to identify the core principles of Islamic communication and their relevance to organizational practices. The findings reveal that four fundamental Islamic values—amanah (trustworthiness), ṣidq (truthfulness), tablīgh (clear and responsible communication), and faṭānah (wisdom and competence)—serve as essential pillars for effective organizational communication. These values promote transparency in decision-making, strengthen mutual trust among organizational members, encourage accountability, reduce communication conflicts, and create a collaborative work environment characterized by justice, integrity, and respect. Furthermore, integrating these principles contributes not only to organizational effectiveness and employee engagement but also to the cultivation of a spiritually grounded organizational culture that aligns professional responsibilities with moral accountability. This study contributes to the growing discourse on Islamic organizational communication by proposing a conceptual framework that integrates ethical, professional, and spiritual dimensions into communication practices. The proposed model offers practical implications for educational institutions, public organizations, and Islamic-based enterprises seeking to establish communication systems that are both effective and ethically sustainable while advancing organizational excellence through Islamic values.